Application and prospect analysis of chimeric antigen receptor T-cell therapy in hepatocellular carcinoma treatment: a systematic review and meta-analysis - Wu, Sichang; Gan, Xinli; Huang, Shuxin; Zhong, Yujun; Wu, Jialin; Yang, Haojie; Xiang, Bangde (Frontiers in Immunology, 2025)
IntroductionHepatocellular carcinoma (HCC), accounting for 90% of primary liver cancers, is a high-mortality malignancy and the third leading cause of cancer-related deaths globally, with major risk factors like hepatitis B/C, aflatoxin exposure, and obesity. Most patients are diagnosed at advanced stages, with a 5-year survival rate below 10%. Therefore, HCC treatment and research still face significant challenges, and more effective treatments need to be further explored.MethodsWe searched PubMed, Scopus, Web of Science and Embase from the time of repository construction to March 1, 2025, preliminary included studies involving animal experiments on the therapeutic effects of Chimeric Antigen Receptor T-cell (CAR-T cell) therapy on HCC. After exclusion and evaluation of literature, the random/fixed effects model was employed to perform meta-analysis and obtain Weighted Mean Difference (WMD) and 95% confidence interval (CI) of tumor volume and mass. We then verify the robustness of the results through subgroup analysis and sensitivity analysis. Use Q-test to evaluate heterogeneity and quantify it based on I² value.ResultsWe included a total of 16 studies. Multiple independent sets of data were extracted from the experiments of these studies, of which 25 were used for volume-based meta-analysis and 16 were used for mass-based meta-analysis. Regarding volume, The combined mean CAR-T treatment group/control group resulted in an WMD of -515.77 (95% CI: -634.78 to -396.76; I² =90.8%). Meanwhile, based on mass, the combined mean CAR-T treatment group/control group resulted in an WMD of -0.30 (95% CI: -0.38 to -0.22; I² = 94.4%). The results of the bias analysis further validated the reliability of the research conclusions.ConclusionsBased on the dual-index meta-analysis, the CAR-T therapy have been proved to possess significant therapeutic effect in HCC. However, the funnel plot of tumor mass and the Egger’s regression suggest the potential presence of publication bias. Thus, it warrants further research to evaluate the potential of CAR-T therapy alone or as an adjuvant for HCC treatment.